La saisie des compétences dans l’interprétation de l’activité de travail - Bulea, Ecaterina; Bronckart, Jean-Paul (My University, 2006)
The first part of this article analyzes the contexts in which the notion of competence first emerged, namely those of professional practice and of the scientific study of work processes; given that in the latter's different theoretical frameworks the problem of competence is intimately linked to that of action, the analysis extends to the way competential dimensions have been conceptualized in the theories of action in philosophy and the social sciences. The second part presents the results of empirical analysis of interviews with nurses on the subject of an occurrence of their nursing practice. A first approach brings out the different action figures put forward by the nurses, as well as the dependence of these figures on the discursive choices operated during the interviews. A second approach focues on the nurses' representations about competence; it shows that the nurses always refer to it in the context of a global analysis of their practice situations, and that they conceive it as a dynamic mobilisation of ressources, oriented by the search of increasing coherence and meaning in their professional activity.
Keywords: action; competence; dynamic; professional practice; action figures